Actualization Of Customary Law (Living Law) As A Form Of Legal Reform In Indonesia - Alfin Aslichatul Ummah (Socio Legal and Islamic Law, 2023)
The nation is the most important entity in a country; without it, there can be no state. In other words, the nation is the fundamental element of a state. The life of a nation is closely tied to its culture, as Aristotle put it, "zoon politicon," a social creature, whereby social interactions lead to agreements that eventually generalize into culture. Similarly, according to Hans Kelsen, a figure in positivism, law originates from societal interactions. In fact, customary law is an ideal source of law because laws already existing within society are unlikely to encounter significant resistance, unlike laws imposed by rulers, which tend to face considerable opposition from the populace.  Keywords: nation, law, customary law